Pengaruh Pembelajaran Aktif Berbantuan Media Wayang Kertas Terhadap Ketrampilan Berbicara Siswa - Anisa, Fitri (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the active learning model assisted by paper puppetmedia on the speaking skills of third grade students at Surodadi 3 Candimulyo StateElementary School, Magelang Regency. This study uses a pre-experimental design methodof the type of one group pretest-posttest. The population in this study were all third gradestudents at SDN Surodadi 3 Candimulyo, totaling 17 students. The research subjects wereselected using a saturated sampling technique. The method of data collection is done byusing a performance assessment. The validity test of the performance assessmentinstrument was carried out using expert validity. The analysis prerequisite test consists ofa normality test and a hypothesis test. Data analysis used parametric statistical techniques,namely the paired sample T-Test test with the help of the SPSS version 22 for windowsprogram. The results of data analysis using the paired Sample T-test showed a significancevalue (2-tailed) 0.000 <0.05. Based on the results of data analysis, the average pretest score was 60 while the posttest score was 74. These results showed an increase in the pretest-posttest score of 23%. The results of the study concluded that the use of active learning models assisted by paper puppet media had an effect on students' speaking skills.